EFFORTS TO BUILD A WOMEN- AND ELDERLY-FRIENDLY MOSQUE: A CASE STUDY AT MASJID AGUNG DARUL FALAH PACITAN - Islam, Fatima; Choirul Hudha, Mokhamad (Al-Mubin, 2025)
This study aims to provide a comprehensive analysis of the initiatives undertaken by Masjid Agung Darul Falah (MADF) in Pacitan to develop a mosque that is inclusive and accommodating for women and the elderly. In communities where religious spaces often marginalize vulnerable groups, mosque-based empowerment models are highly relevant. A mosque should not only serve ritual purposes but also function as a center of social transformation for all members of society. Employing a qualitative approach with a case study method, data were collected through participant observation, in-depth interviews with mosque administrators and congregants, as well as documentation of community activities. The findings indicate that MADF has implemented inclusive programs such as regular religious classes, Qur'anic literacy training, the Bina Lansia (Bilas) initiative, group health exercises, and daily charity activities managed by female congregants. Youth-oriented programs, including weekly discussions, Ngopi Hijrah sessions, and certified Qur’anic literacy (BTA) training, also play a significant role in engaging young women. These results highlight that participatory approaches and collective awareness are crucial in fostering mosques that are friendly to both women and the elderly. The study recommends that this model be replicated in other regions, supported by policy frameworks and institutional capacity development